Visual Discourse of Comics in English Language Teaching - Razvan Radan (Yayasan Visi Intan Permata, 2017)
This article discusses the findings of theoretical research on visual communication and comic book discourse that aimed to identify viable approaches for English language teaching based on comics. Comics are one type of creative text that can have the same complexities or intricacies as for example a novel. One problem identified in SLT is that while creative texts are used in teaching, the focus is on the written word - novels, short stories, poems. Few if any teaching approaches promote the use of comics in the classroom environment. If comics are suggested as teaching materials, the recommended approach is very similar to that used when dealing with non-visual texts. As a consequence, students tend to ignore the images and thus miss out a possible avenue that can help with meaning making. There is then a need for a better understanding of how visual communication works in comics and how meaning is created from the interplay of image and text. This article examines how visual communication happens, what are the elements of a visual narrative and then continues to identify the elements that form the comic book discourse. Using a framework based on the theories that identify and explain the workings of the structural elements of a panel as well as the social function of visual communication this researcher discusses how comics communicate to their readers. The findings suggest that in order to develop a methodology and to successfully use comics in teaching, the educator needs to rethink the current practices when dealing with comics or any other